(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-68-80 The main communicative strategies and their implementing tactics were revealed in German newspaper interviews devoted to the events in Ukraine in March – May 2022. The main communication strategies in this genre of German media are the information and interpretation strategy, the strategy of the reader’s emotional mood and the strategy of self-presentation. The most common lexical units, lexico-stylistic and syntactic-stylistic means that implement basic communicative tactics in interview texts are established. Key words: communicative strategy, communicative tactics, evaluation, value, journalist, word, text, interview